Good Governance: Bojongmalaka Village Fund, Baleendah District, Bandung Regency, Indonesia - Engkus Engkus; Anisya Septa Pitaloka (Department of Public Administration, 2023)
Bojongmalaka Village has the authority to manage village funds tailored to the community's needs in developing and empowering village communities. The governance of village funds is regulated by applicable laws and regulations, starting from planning, implementation, administration, reporting, and accountability. The problem in this research is that in planning village funds, elements of the community are not included in the preparation of the Village Government Work Plan (RKPDes), the implementation process is still not following applicable laws and regulations, and their accountability to the community is not maximized. This study aimed to find out and describe the financial management of village funds in Bojongmalaka Village, Baleendah District, Bandung Regency. This study uses a qualitative method with a descriptive approach. Observation, interviews, and documentation used data collection techniques. Data analysis techniques that researchers do with the stages of data reduction, data presentation, and conclusion. The results of the study revealed that the financial management of village funds in the village of Bojongmalaka was still not optimal in planning, implementation, and accountability, even though the administration was by applicable regulations and in reporting the realization of the APBDes there was never a delay to the local government through the sub-district